Efficacy of Bioinsecticides against the Hop Aphid Phorodon Humuli (Schrank) (Hemiptera: Aphididae) under Laboratory Conditions - Vasilev, Pavlin; Atanasova, Daniela; Andreev, Radoslav (Canadian Journal of Agriculture and Crops, 2019)
The efficacy of three bioinsecticides: the microbial Naturalis (Beauveria bassiana) and the botanical Pyrethrum FS EC (pyrethrin + sesame oil + soft potassium soap) and NeemAzal T/S (azadirachtin), allowed for application in organic farming in Bulgaria, against the hop aphid Phorodon humuli Schrank were studied under laboratory conditions. The best results from the tested products showed microbial insecticide Naturalis (Beauveria bassiana). At a concentration of 0.2% the efficacy reached 46% on the 3-rd day, 70.3%, on the 5-th day and 91.5% on the 7-th day after the treatment. The preparation showed very good action in its low concentration (0.1%) – efficacy was over 65% on the 5-th day and 79.8% on the 7-th day after the treatment. Insecticides based on plant extracts showed not very good efficacy against P. humuli. The Pyrethrum insecticide, based on natural pyrethrins showed better action than azadirachtin based product NeemAzal T/S. The efficacy of Pyrethrum on the 7-th day after the treatment reached 86.9% at concentration 0.1% and 75.8% at lower concentration of 0.05%. The weakest action showed NeemAzal T/S. The efficacy was only 67.6% and 61.6% at concentration 0.5% and 0.3%, respectively.